Giving an Identity: Coordinates of Invention. Heresy and Dissidence Among Non-Philosophers - Aksayam, Narciso (Identities: Journal for Politics, Gender and Culture, 2018)
Not known enough for his former publications in philosophy, François Laruelle’s attempt to institute a democratic field for all hermeneutic content and every philosophical knowledge is not that easy to re-enact starting from the Nietzschean and Levinassian apparatus of his early thought, and considering the refusal of reciprocity that is correlated with his theory of Unilaterality. This difficulty also manifests in the résumé of his philosophical career. Though presented for a long time as solitary, Laruelle recently acknowledged that his work had been built within the dynamic of colleagues and disciples as well. From there, an insight on the intersubjective past of non-philosophy will unfold the coextensive network of affects that are part of its construction as a matrix of Democracy. And since Heresy is one of the major figures of Laruelle’s thought, it is interesting to pay attention to how dissidences have been dealt with in his own discourse and posture while non-philosophy was emerging as an intersubjective assemblage. Two historical characters will be considered: Serge Valdinoci, an early collaborator in the 1980s, who built a specific method of immanence, europanalysis, and who distanced himself from non-philosophy at the turning of Philosophy III; and Gilles Grelet, a prominent disciple in the 1990s, who co-founded Organisation Non-Philosophique Internationale (ONPhI) with Ray Brassier, and who played such a major role in non-philosophy that it drove Laruelle to write Struggle and Utopia at the End Times of Philosophy. Author(s): Narciso Aksayam Title (English): Giving an Identity: Coordinates of Invention. Heresy and Dissidence Among Non-Philosophers Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 15, No. 1-2 (Summer 2018) Publisher: Institute of Social Sciences and Humanities – Skopje Page Range: 118-156 Page Count: 39 Citation (English): Narciso Aksayam, “Giving an Identity: Coordinates of Invention. Heresy and Dissidence Among Non-Philosophers,” Identities: Journal for Politics, Gender and Culture, Vol. 15, No. 1-2 (Summer 2018): 118-156.